The Effect of Implementing EMR on User Acceptance of Electronic Medical Records based on The Unified Theory of Acceptance and Use of Technology (UTAUT) 2 in Hospital - Bachtiar, Silvani; Baktiar, Rahmat; Sedionoto, Blego (Mulawarman International Conference on Tropical Public Health, 2025)
The Ministry of Health requires every health facility in Indonesia to maintain electronic medical records based on Minister of Health Regulation (Permenkes No.24/2022). However, the use of EMR in Indonesia still finds many obstacles in user acceptance based on UTAUT 2 method. This research aims to assess the implementation of EMR on user acceptance in hospitals. The research uses a literature review method by reviewing 30 journal articles published between 2020 until 2024, which were retrieved via Google Scholar. 4 eligible articles were selected. The results show that there are factors that influence user acceptance based on the UTAUT 2 Model, which is performance expectations, effort expectations, social influence, facilitating conditions, hedonic motivations, price values and habits influence the behavior intentions and Use Behavior of EMR users. In several studies, there are moderating variables such as age, gender and work experience that influence the relationship between constructs that build user intentions and behavior. This research to encourage all health facilities to carry out evaluations in optimizing the use of EMR.